THE EFFECT OF JOB TRAINING , INDEPENDENCE, AND GOVERNMENT SUPPORT ON WOMEN'S ENTREPRENEURIAL INTEREST IN UPTD LK, ENDE REGENCY - Gabriel Tanusi; Graciana Yulia Agustina (SEAN Institute, 2022)
This study aims to determine and partially analyze the effect of job training, independence, and government support factors on the entrepreneurial interest to female jon training participants in UPTD LK Ende. The type of research is associative. The research population is 64 female job training participants. The sampling technique uses saturated sample with a total of 64 female job training participants. Date collection techniques using questionnaires and interviews. Date analysis technique using multiple linear regression analysis. The results showed that partially the job training factor has a positive and significant effect on the entrepreneurial interest of job training participants at UPTD LK Ende, The independence factor has a positive and significant effect on the entrepreneurial interest of job training participants at UPTD LK Ende